Heart stem cells: fact or fantasy? - E. V. Parfenova (Российский кардиологический журнал)
In the  spring  of 2018,  Harvard Medical School  and  the  Brigham and  Women’s Hospital reported  the retraction  of 31 articles of Dr. Piero Anversa lab, who have been  studying heart stem cells for more than 15 years,  due to the fact that these articles  “included  falsified  and/or   fabricated   data”.  This extremely  unpleasant incident cast  suspicion on other research groups  studying regenerative  effects  ofcells harvested  from the myocardium. It contributed  to skeptical opinion about thepossibilities of regenerative  technologies in cardiology in general and the complete denial of any regenerative  potential of heart. This review presents an analysis of Dr. Piero Anversa lab studies  and  other  works devoted  to the study of regenerative processes in the heart, a modern view on the mechanisms of the heart regenerative potential and the regenerative  effects of progenitor cells harvested  from the myocardium,  and  the  prospects for the  development  of cellular technologies in cardiology.